The Effect of Sustainability Report on Financial Performance With Firm Size as a Moderation Variable - Julianingtyas, Bunga Nur; Suprianto, Edy (Universitas Islam Sultan Agung, 2025)
Abstract. This study examines the effect of sustainability reports on financial performance with firm size as a moderating variable. The independent variable is the Sustainability Report which is measured using GRI standards. The dependent variable is financial performance as measured using ROA. The Moderating Variable is firm size as measured using LnTotal Assets. The research sample consists of banking companies listed on the Indonesia Stock Exchange during 2020-2023. Purposive sampling method was used to determine the research sample. The sample used was 15 companies in the 2020-2023 period. Data obtained from the Sustainability report and the Company's annual report. Data processing uses STATA 17. The results of this research show that sustainability reports have a positive and significant effect on financial performance, while company size as a moderating variable is not significant on the relationship between sustainability reports and financial performance.